Exploring the Relationship Between Multi-Dimensional Top Management Support and Project Success: An International Study. Issue 1 (2nd January 2016) - Ahmed, Riaz; Azmi bin Mohamad, Noor
Abstract: The role of top management support in achieving project success has gained much attention in research and practice. A number of studies on single dimensional top management support have been conducted. In the engineering management literature, top management support has rarely been studied as a multi-dimensional construct. This research examines the relationship between multiple dimensions of top management support and project success. Different data analysis methods were employed to test the research hypotheses and to validate the multi-dimensionality of top management support. Findings indicate a significant and positive relationship between multi-dimensional top management support and project success.